Some issues of legislative regulation of the institution of judicial representation in the Republic of Kazakhstan - Zhamburbayeva, S.; Ilyassova, G.A. (Bulletin of the Karaganda University “Law Series”, 2022)
The legal regulation of the institution of representation should correspond to the trends in developing the country’s legal system. This is feasible if problems in law enforcement are not only identified but also elimi-nated, which will positively affect the effectiveness of the subjects’ realization of their civil rights and obliga-tions. Gaps in the legislation that regulate the institution of representation exist, as in any other legal phenomenon. This is evidenced by the fact that despite the adoption of the Law “On Advocacy and Legal Consult-ants”, issues of judicial representation in the legal community continue to be actively discussed. In particular, attention is drawn to disputes about the legal status of judicial representatives — legal consultants, which have been actualized after the modernization of legislation. Equally important are questions about the quality of professional services provided by these subjects, which often arise due to their abuse of procedural rights, as well as negligent attitude towards the obligations they have assumed. No less controversial is the issue of self-regulation of chambers of legal advisers, which generates a lot of controversy regarding the competitive-ness of members of these chambers. The authors of this research attempted to analyze the identified issues, examined the opinions of legal scholars about the nature of emerging discussions, and also suggested ways to solve them to improve the current legislation in the field of representation in court.